EXPLORING CROWDFUNDING POTENTIAL FOR SUPPORTING COMMUNITY- BASED TOURISM IN MALAYSIA (International Journal of Islamic Business, 2022)
This paper discovers the potential of the Islamic crowdfunding model for supporting community-based tourism in developing states Malaysia in particular. Community-based tourism has provided a great opportunity for rural areas to empower the socio-economy of local people to earn main or additional income, and crowdfunding is seen as a potential fund for supporting community-based tourism. This study applies a library research method as its data are collected through literature related to community-based tourism and crowdfunding topics. The special model of Islamic crowdfunding proposed by this study can potentially support community-based tourism if it is applied to a real platform. As a result, it can reduce the burden of the government in providing funds for tourism. While crowdfunding creates an alternative opportunity for community and tourism-based projects, it promotes job opportunities and economic growth within society including business and services. However, this approach could be challenging to apply because of awareness among people. Nevertheless, a suitable Islamic crowdfunding model with a proper campaign can be a practical solution for funding community-based tourism projects. As this study is conceptual, the outcomes may not be limited. However, it still provides a substantial contribution in terms of offering a practical model of Islamic crowdfunding in Malaysia.